Myocardial Dysfunction after Severe Food Restriction Is Linked to Changes in the Calcium-Handling Properties in Rats - Deus, Adriana Fernandes de [UNESP]; Silva, Vitor Loureiro da [UNESP]; Borges de Souza, Sergio Luiz [UNESP]; Ferreira Mota, Gustavo Augusto [UNESP]; Sant'Ana, Paula Grippa [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Lima-Leopoldo, Ana Paula; Leopoldo, Andre Soares; Salome de Campos, Dijon Henrique [UNESP]; Tomasi, Loreta Casquel de [UNESP]; Padovani, Carlos Roberto [UNESP]; Kolwicz, Stephen C.; et al. (Mdpi, 2019)
Severe food restriction (FR) impairs cardiac performance, although the causative mechanisms remain elusive. Since proteins associated with calcium handling may contribute to cardiac dysfunction, this study aimed to evaluate whether severe FR results in alterations in the expression and activity of Ca2+-handling proteins that contribute to impaired myocardial performance. Male 60-day-old Wistar-Kyoto rats were fed a control or restricted diet (50% reduction in the food consumed by the control group) for 90 days. Body weight, body fat pads, adiposity index, as well as the weights of the soleus muscle and lung, were obtained. Cardiac remodeling was assessed by morphological measures. The myocardial contractile performance was analyzed in isolated papillary muscles during the administration of extracellular Ca2+ and in the absence or presence of a sarcoplasmic reticulum Ca2+-ATPase (SERCA2a) specific blocker. The expression of Ca2+-handling regulatory proteins was analyzed via Western Blot. Severe FR resulted in a 50% decrease in body weight and adiposity measures. Cardiac morphometry was substantially altered, as heart weights were nearly twofold lower in FR rats. Papillary muscles isolated from FR hearts displayed mechanical dysfunction, including decreased developed tension and reduced contractility and relaxation. The administration of a SERCA2a blocker led to further decrements in contractile function in FR hearts, suggesting impaired SERCA2a activity. Moreover, the FR rats presented a lower expression of L-type Ca2+ channels. Therefore, myocardial dysfunction induced by severe food restriction is associated with changes in the calcium-handling properties in rats.
Keywords: malnutrition; heart impairment; papillary muscle assay; calcium transient proteins; SERCA2a; L-type calcium channel